Coercion Resistance in Authentication Responsibility Shifting - GUPTA, Payas (Institutional Knowledge at Singapore Management University, 2012)
Responsibility shifting, a popular solution used in the event of failure of primary authentication where a human helper is involved in regaining access, is vulnerable to coercion attacks. In this work, we report our user study which investigates the helper’s emotional status when being coerced to assist in an attack. Results show that the coercion causes involuntary skin conductance fluctuation on the helper, which indicates that he/she is nervous and stressed. This response can be used to strengthen the security of the authentication system by providing coercion resistance.